Building competitive regions strategies and governance. - ProQuest (Firm) (Paris : OECD, 2005)
In recent years, the main focus of territorial policy has been on sustaining growth, not only to address relative decline, but also to make regions more competitive. Putting this in practice is complicated because different regions have different characteristics (urban, intermediate, industrial, rural, etc.), which imply specific policy and investment needs. This report assesses the strategies pursued by OECD member governments to address the competitiveness of regional economies and the accompanying governance mechanisms on which the implementation of these strategies rests. The report is principally based on findings from the series of reviews undertaken by the OECD Territorial Development Policy Committee at national and regional levels.--Publisher's description.
pt. 1. Strategies: Competitiveness in a regional context ; Competitive firms : policies to generate innovation and knowledge ; Competitive regions : policies for the wider business environment -- pt. 2. Governance: Coordination between the different levels of government : transfers, contracting practices and incentives ; Horizontal co-ordination ; New actors in economic development strategies ; Common issues in co-operative governance.
Also published in French: Promouvoir la competitivite des regions : strategies et gouvernance.
Includes bibliographical references (p. 135-140).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Economic development; Regional economics; Competition; Electronic books